IMPACT OF EPS, INTEREST RATE, ROE, NIM, AND INFLATION ON STOCK PRICES IN IDX - Silvi Wijaya; Cindy Cynthia; Jholant Bringg Luck Amelia Br Sinaga (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2021)
This study looked at how much Earnings Per Share (EPS), interest rates, Return on Equity (ROE), Net Interest Margin (NIM), and inflation had on stock prices at the same time. This type of research uses a quantitative approach because the data used is numbers and the method used is the multiple linear regression method. The banking sector's population is 45 companies, chosen using a purposive sampling technique, so the number of samples studied was 22, with a total of 66 samples collected over a three-year period. The result of Adjusted R Square is 0.750 with the intention that 75% of the independent variables (EPS, interest rate, ROE, NIM, and inflation) affect the dependent variable (stock price) while the remaining 25% is explained by other variables. According to the observation results, EPS and NIM have a positive and significant effect on stock prices, the interest rate has a negative and insignificant effect on stock prices, ROE has a negative and significant effect on stock prices, and inflation has a positive and insignificant effect on stock prices.Simultaneously, EPS, interest rates, ROE, NIM, and inflation have a significant effect on stock prices in banking companies listed on the Indonesia Stock Exchange in 2017-2019